Manajemen Pendidikan di Indonesia dalam Menghadapi Era Digital: Kajian Literatur atas Strategi dan Tantangan - Mariatul, Mariatul (Pusat Riset dan Inovasi Nasional, 2025)
Technological development undoubtedly affects various aspects of life, with technology being introduced to provide convenience and save time. In response to the changing times, society must grow and adapt accordingly. Educational digitalization is a form of adaptation to technological advancement, aiming to facilitate access to knowledge. However, several challenges must be addressed in this digital era, such as unequal access to technology, limited devices and network infrastructure, and the varying readiness of human resources. This research employs a qualitative approach using the library research method. This method was chosen to allow the researcher to review and analyze relevant sources in order to understand how educational management can respond to the challenges posed by digital transformation. In Indonesia, educational digitalization is no longer merely a technical issue but has become part of the national policy agenda, as it plays a key role in the broader transformation of the education system. To face these challenges, educational management is required to take on a strategic role in designing and implementing policies that can effectively respond to ongoing issues. While digitalization offers various conveniences and efficiencies, its implementation still faces considerable obstacles, particularly in terms of infrastructure readiness, the competence of human resources, and school-level management capacity.